2007
DOI: 10.1007/s10886-007-9353-7
|View full text |Cite
|
Sign up to set email alerts
|

Root-secreted Allelochemical in the Noxious Weed Phragmites Australis Deploys a Reactive Oxygen Species Response and Microtubule Assembly Disruption to Execute Rhizotoxicity

Abstract: Phragmites australis is considered the most invasive plant in marsh and wetland communities in the eastern United States. Although allelopathy has been considered as a possible displacing mechanism in P. australis, there has been minimal success in characterizing the responsible allelochemical. We tested the occurrence of root-derived allelopathy in the invasiveness of P. australis. To this end, root exudates of two P. australis genotypes, BB (native) and P38 (an exotic) were tested for phytotoxicity on differ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

10
105
0
1

Year Published

2013
2013
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 122 publications
(119 citation statements)
references
References 49 publications
10
105
0
1
Order By: Relevance
“…This experiment showed a substantial reduction of root length, biomass, and several ecophysiological parameters. These results are consistent with several studies which found that P. australis lowered the root biomass of endemic Eriocaulon carsonii due to belowground competition (Davies et al 2010) and showed negative effects on the germination and establishment of Arabidopsis thaliana in vivo conditions while conversely showing a positive effect under AC treatment (Rudrappa et al 2007). Our previous study found that P. australis rhizosphere and infested soil contained total phenolics with a concentration of 1.17 and 1.26 mg g (1 , respectively, that might be enough for an inhibitory effect on the associated plant species (Uddin et al 2012).…”
Section: Discussionsupporting
confidence: 92%
See 4 more Smart Citations
“…This experiment showed a substantial reduction of root length, biomass, and several ecophysiological parameters. These results are consistent with several studies which found that P. australis lowered the root biomass of endemic Eriocaulon carsonii due to belowground competition (Davies et al 2010) and showed negative effects on the germination and establishment of Arabidopsis thaliana in vivo conditions while conversely showing a positive effect under AC treatment (Rudrappa et al 2007). Our previous study found that P. australis rhizosphere and infested soil contained total phenolics with a concentration of 1.17 and 1.26 mg g (1 , respectively, that might be enough for an inhibitory effect on the associated plant species (Uddin et al 2012).…”
Section: Discussionsupporting
confidence: 92%
“…The presence of gallic acid in root exudates of P. australis was previously reported by Rudrappa et al (2007), but no relative abundance among organs was studied in details. The present study confirmed the rank of abundance among different organs.…”
Section: Discussionmentioning
confidence: 97%
See 3 more Smart Citations